Effect of sewage sludge fertilization in short‐rotation willow plantations - Dagnija Lazdiņa; Andis Lazdiņš; Zigurds Kariņš; Visvaldis Kāposts (Journal of Environmental Engineering and Landscape Management, 2007)
The aims of the research work were to evaluate increase of productivity of Salix energy crop and forest plantations by using sewage sludge fertilization, impact of sewage sludge on the environment, and to calculate economic income from plantations. The most important problem during the first rotation cycle in willow plantations was weed control. After using sludge weeds grew up, because sludge contains large amounts of nutrients. After cutting of sprouts in the second growth season willow plantations produce more sprout from stand, and productivity increases from 0,2–0,6 t to 4,6–5,5 t of dry mass/ha. Effect of sewage sludge fertilization is greater in the second season both in control plantations and fertilized plantations. Average biomass production in fertilized plantations was 5,5 t of dry mass/ha per year. Shoot wood from fertilized plantations contained on the average by 4–8 % more heavy metals than control plantation wood. The concentration of heavy metals in the top soil layer increased, but it did not exceed the Regulations issued by the Cabinet of Ministers of Latvia about the soil quality, and the soil cultivation in the first three years was 760 LVL/ha. If the distance were not longer than 40 km and a willow‐cutting combine operated without pauses, costs for cutting, chip crushing and delivery to consumers would achieve 4 LVL/m3.